FRI0040 Transitional zones displacement of the subchondral bone layers in a model of osteoporosis and osteoarthritis in rabbits. (23rd January 2014) - Castañeda, S.; Guede, D.; Caeiro, J. R.; Roman-Blas, J. A.; Largo, R.; Herrero-Beaumont, G.
Abstract : Background: Subchondral bone (SB) plays a crucial role in osteoarthritis (OA) pathogenesis. Nevertheless, there is little information available about the microarchitectural characteristics of the different layers and transitional zones (TZ) comprising the SB. In previous experiments in animals, we have confirmed that an increased SB remodeling may account for the aggravation of cartilage damage in OA rabbits with previous osteoporosis (OP) that was reversed improving SB quality. Objectives: To analyze, through micro-CT, the microstructural characteristics of the different SB layers in our OP and OA model to determine the effect of the microarchitecture of SB in the OA severity. Methods: Experimental OA was induced in 12 female NZ white rabbits (8 months old; weight 3.5-5 kg) by ACLT and partial medial meniscectomy (OA) in the left knees. In 6 of them, OP was previously induced by bilateral oophorectomy and subsequent prednisolone administration, 1 mg sc/kg/d for 5 wks (OPOA knees). Right knees of OPOA were used as OP knee controls, while right knees of OA group were used as healthy knees. After sacrifice, knees of both groups were carefully dissected for later analysis. With this objective, cylindrical samples of SB (4 mm in diameter by 9 mm in length) were extracted from femoral condyles. The microarchitectural characteristics of the samples were studied using micro-CT with a SkyScan 1172 (Bruker micro-CT NV). Morphometric parameters were calculated "slice-by-slice" on all individual cross-sections in order to visualize the profile of each variable along the length of the sample. Furthermore, the thickness of the first layer of bone (SB plate, SBP) was determined assuming for this layer a porosity <2%. As it showed a non-normal distribution, the statistical comparison was performed using the Kruskal-Wallis H test, and post-hoc analysis using Dunn's test. Results: According to the bone area fraction (B.Ar/T.Ar) profile at least 3 bone layers can be clearly characterized at SB: the SBP, a dense trabecular bone (trabecular SB) and the subarticular trabecular bone. Furthermore, 2 different TZ between these layers could be distinguished. SBP thickness was diminished both in OP and OA groups with respect to healthy (p<0.05 in both cases). OPOA group revealed an additional reduction of the SBP thickness showing also significant differences vs. other groups (p<0.05). Some of the other variables analyzed show the same behavior in their profiles, distinguishing the 3 bone layers mentioned above. It is the case for Tb.Th, Tb.Sp, Tb.N, polar moment of inertia and Tb.Pf. As well, the dispersion curves of the different parameters analyzed showed always a consistent and concordant displacement of the TZ toward the joint surface in all the groups. Conclusions: In this work, it seems to predict the existence at least of three different microstructural layers at SB level and 2 different TZ between them which must be confirmed by mathematical modeling. As well, there was a clear and concordant displacement toward the superficial areas of the joint in all experimental groups, transforming the biomechanics of SB that might partially explain the OA aggravation in rabbits with previous OP. We think these findings are of great interest for a therapeutic approach of patients with OA and OP associated. Disclosure of Interest: None Declared